2011
DOI: 10.1590/s1517-86922011000200013
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de oxigênio de recuperação em resposta a duas sessões de treinamento de força com diferentes intensidades

Abstract: O objetivo do presente estudo foi comparar o comportamento do consumo de oxigênio (VO2) em resposta a uma sessão de treinamento de força (TF) com objetivo em hipertrofia muscular (HP) com uma sessão com objetivo em resistência muscular localizada (RML). Nove indivíduos do sexo masculino (23,1 ± 2,1 anos) foram recrutados para este estudo. A força muscular dinâmica foi mensurada através do teste de 1RM. O VO2 foi coletado durante o repouso e 10 minutos de recuperação com um analisador de gases (CPX/D). As sessõ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…In the present systematic review, we found three studies (Kirk et al , ; Almeida et al , ; Cesar et al , ) using high intensities (between 80–90% 1RM) in their ST protocols. Kirk et al () verified the effect of high intensity and low volume (1 set; 3 days per week; 3–6 repetition; 85–90% of 1RM; 9 exercises) in EE.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In the present systematic review, we found three studies (Kirk et al , ; Almeida et al , ; Cesar et al , ) using high intensities (between 80–90% 1RM) in their ST protocols. Kirk et al () verified the effect of high intensity and low volume (1 set; 3 days per week; 3–6 repetition; 85–90% of 1RM; 9 exercises) in EE.…”
Section: Discussionmentioning
confidence: 74%
“…According to the studies presented in (Table 2), 75% assessed the intensity in percent values comprised between 50 and 75% (moderate) of one maximum repetition (%1RM) while, three studies (Kirk et al, 2009;Almeida et al, 2011;Cesar et al, 2013) (25%) addressed vigorous intensity > 80% 1RM and three studies (Hunter et al, 2003;Kirk et al, 2009;Scott et al, 2009) (18%) involved an intensity lower when compared with 50% 1RM.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been analyzing the physiological responses of exercises of different intensities, what is perceived is that the data obtained from them are, many times, controversial because some [25][26][27] suggest there is no difference between the variables analyzed, while others suggest that there is difference between the protocols. [28][29][30] Analyzing all the data and comparing them with many studies it is perceived that the EPOC and the energetic expenditure in recuperation vary according to the type of exercise being practiced, the volume, and intensity applied in the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The indication of strength training (ST) as a non-pharmacological strategy in the prevention and treatment of obesity is currently considered effective and efficient. 1 Significant increases in oxygen consumption and consequently in energy expenditure (EE), depending on variables such as muscle mass, 2 lifting tempo, 3 number of sets, 4 number of repetitions, 5,6 training load, 7 training volume, 8 or recovery intervals, [9][10][11][12] have been widely investigated and used on the basis of exercise prescription.…”
Section: Introductionmentioning
confidence: 99%